Coelogin ameliorates metabolic dyshomeostasis by regulating adipogenesis and enhancing energy expenditure in adipose tissue. (October 2021) - Gupta, Sanchita; Mishra, Tripti; Varshney, Salil; Kushawaha, Vinita; Khandelwal, Nilesh; Rai, Prashant; Garg, Richa; Dev, Kapil; Gupta, Abhishek; Kumar, Durgesh; Balaramnavar, Vishal M.; Arya, Kamal Ram; et al.
Abstract: Obesity and associated metabolic disorders are heading up with an alarming rate in developing nations. One of highly sought solution for metabolic disorders is to identify natural molecule with an ability to reduce obesity and increase insulin sensitivity. Coelogin (CLN) is a phenanthrene derivative isolated from the ethanolic extract of Coelogyne cristata . In our constant efforts to identify novel anti-dyslipidemic and anti-adipogenic compounds using CFPMA (common feature pharmacophore model using known anti-adipogenic compounds) model, predicted possible anti-adipogenic activity of CLN. In vitro results showed significant inhibition of adipogenesis in 3T3-L1 and C3H10T1/2 cell by CLN. It arrests the cell cycle in G1 phase of interphase and inhibits mitotic clonal expansion to regulate adipogenesis. CLN elicits insulin sensitizing effect in mature adipocytes. During extracellular flux assessment studies, it increases oxidative respiration and energy expenditure in adipocytes. In vivo, CLN reversed HFD-induced dyslipidemia as well as insulin resistance in C57BL/6 mice. It promoted the expression of genes involved in improved mitochondrial function and fatty acid oxidation in eWAT. CLN restored energy expenditure and increased the capacity of energy utilization in HFD fed mice. Taken together, the study indicated beneficial effects of CLN in combating obesity-associated metabolic complications. Graphical Abstract: ga1